Depression, Socioeconomic Factors, and Ethnicity as Predictors of Cardiorespiratory Fitness Before and After Cardiac Rehabilitation. Issue 4 (July 2019) - Mikkelsen, Nicolai; Dall, Christian Have; Frederiksen, Marianne; Holdgaard, Annette; Rasmusen, Hanne; Prescott, Eva
Abstract : Purpose: To determine whether cardiac patients with psychosocial or socioeconomic problems have lower peak oxygen uptake ( O2peak ) and whether these factors modify the effect of cardiac rehabilitation (CR). Methods: A retrospective cohort study of patients with ischemic heart disease, valvular heart disease, or heart failure referred for CR. O2peak was assessed by a maximal cardiopulmonary exercise test. Pre-existing depression was defined by use of antidepressants and new-onset depression by a modified Primary Care Evaluation of Mental Disorders (PRIME-MD) questionnaire at CR intake. Socioeconomic status was defined by educational attainment and working status; ethnicity as Western European or non-Western European. Full data from baseline assessment were available on 1217 patients and follow-up on 861 patients. Results: Mean ± SD O2peak before CR was 21.8 ± 6.8 mL/kg/min. After multivariable adjustment, lower O2peak was associated with lower educational attainment, not working, and non-Western ethnicity but not with depression. Mean improvement of O2peak following CR was 2.4 ± 4.3 mL/kg/min. After multivariable adjustment educational attainment, employment status and ethnicity were significant predictors of improvement of O2peak while depression was not. Conclusion: Education, attachment to the workforce, and ethnicity were all associated with lower O2peak before CR, and the disparity was increased following CR. Having pre-existing depression and new-onset depression did not influence O2peak either before or after CR. These results point to important subgroups in need of specially-tailored rehabilitation programs. Abstract : Supplemental Digital Content is Available in the Text.The level of cardiorespiratory fitness, assessed by the cardiopulmonary exercise test, was related to socioeconomic and ethnic factors, both before and after rehabilitation. These results suggest that important inequalities exist within subgroups of cardiac patients and that this should be accounted for by health care professionals, as patients enter a rehabilitation program.